Temperature anisotropies: covariant CMB anisotropies and nonlinear corrections - Gebbie, Tim (Department of Mathematics and Applied Mathematics, 2019)
The questions I ask myself are generally all along the lines of "so where did all this structure come from?". I hoped that work in the CMB and its cosmological implications would give me insight into this. It is an adventure that is still young. I began my PhD with an investigation of some formal aspects of Ehlers-Ellis Relativistic Kinetic Theory in mind { the implications of the truncation conditions found in the exact theory. I ended up trying to calculate CMB anisotropies as an application of this beautiful and somewhat purist formalism. The Ehler-Ellis (1+3) Lagrangian approach to General Relativity (GR) and Relativistic Kinetic Theory (RKT) are apparently not well known nor well used and have only recently begun to show advantages over the more usual ADM and Bardeen perturbative approaches to astrophysical cosmology when combined with the Ellis Bruni perturbation theory.